(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study on pests protected cables as a strategy for effective prevention of fire outbreak fromelectrical installations in workshops in technical colleges in Rivers State was necessitated bythefrequent fire outbreak from electrical installation in workshops in technical colleges. Aresearchquestion and two null hypotheses guided the study. A descriptive survey research design was employed for the study. The population for this study comprised of 45 electrical teachers in four technical colleges in Rivers State. The entire population was studied without sampling since the sizewas not too large and was manageable. The instrument for data collection was a structuredquestionnaire titled ‘Pest Protected Cables for Effective Prevention of Fire Outbreak fromElectrical Installation in Workshops’. The instrument was validated by two experts from the Departments of Industrial Technical Education and Educational Foundations in Ignatius Ajuru Universityof Education, Port Harcourt. Using the Cronbach alpha method to determine the reliability of theinstrument, the reliability co-efficient of 0.78 was obtained. The data collected for the study wereanalyzed using mean and standard deviation to answer the research questions and to determine thecloseness of the respondents’ mean ratings. The t-test was used to test the null hypotheses at 0.05level of significance. The findings of study revealed that pests protected cables will be very effectivestrategy for prevention of fire outbreak from electrical installations in workshops in technical colleges. The findings also showed that year of experience and location had no significant influence ontheopinion of respondents on the effective of peste protected cables as a strategy for prevention of fireoutbreak from electrical installations in workshops in technical colleges. Based on the findings of this study, it was recommended that pests protected cables should be used during constructionandrenovation of workshops among others.